Agribusiness analysis of seed producer supports increased soybean production in East Java production centre areas - Ruly Krisdiana; Dian Adi Anggraeni Elisabeth; Moh Saeri; Yanti Rina Darsani; Rusli Burhansyah; Juliana Carolina Kilmanun; Umi Karomah Yaumidin; Made Jana Mejaya; Didik Harnowo; Arief Harsono (International Journal of Agricultural Sustainability)
Quality seeds are one of the main technological components for increasing soybean crop production. Until now the use of quality soybean seeds in Indonesia only reaches 30%. The constraints of providing soybean quality seeds still often occur. The objectives of this study are to identify the financial feasibility of soybean seed producer in various uses of soybean products; to identify socio-economic constraints on soybean seed producer and to propose a strategy for developing soybean seed producer agribusiness in East Java province. The survey was conducted on soybean seed growers and soybean farmers who planted soybeans in the 2022 growing season. The results showed that the R/C ratio of producers for seed purposes, producers for consumption purposes, and soybean farmers are 1.34, 1.23 and 1.2, respectively. Threats faced by soybean seed producers include suboptimal post-harvest handling and the rapidly decreasing soybean seed germination. The strategy in developing soybean seed producer that can be proposed are: growing soybean seed farmers at each production centre location to meet the needs of seeds on time, quantity, variety, agroclimate, quality, and price, so as to meet the need of local farmers quickly, and reduce the risk of rapidly decreasing seed germination.